Sistem Informasi Penjadwalan Kegiatan Organisasi Kepemudaan Berbasis Web Di Dinas Pemuda Dan Olahraga Provinsi Gorontalo - Bokings, Nur Fadhila; Koniyo, Moh Hidayat; Padiku, Indhitya R. (Gorontalo State University, 2025)
The Youth and Sports Agency of Gorontalo Province is an institution that supports and mentors youth organizations in Gorontalo Province. Youth organizations actively organize youth activities at the national, provincial, and regional levels. However, the process of submitting proposals and event invitations is currently done by physically delivering hardcopy documents, which takes a long time and makes it difficult to obtain information about the status of the application. With numerous proposals and event invitations submitted, the Youth and Sports Agency faces challenges in verifying the submitted documents. Some youth organizations often propose events to be held at the same or close times, which creates difficulties for the Youth and Sports Agency in prioritizing which activities should be scheduled first. The Multi-Attribute Utility Theory method is applied as a decision-support tool to determine which activity should take precedence. The development of this system utilizes the waterfall model, and testing is conducted using black-box testing. The research result is a web-based youth organization activity scheduling information system that can be used by the Youth and Sports Agency and youth organizations to facilitate the prionitization of event schedules, proposal application and invitation, and activity reporting.